2007
DOI: 10.1111/j.1469-8749.2006.tb01287.x
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the prevalence of cerebral palsy in Northern Ireland, 1981-1997

Abstract: We describe trends in the prevalence of cerebral palsy (CP) by birth weight group, and in the severity of motor impairments and presence of associated intellectual impairment, in Northern Ireland from 1981 to 1997 (n=909; 510 males, 399 females; total population 415 936 live births) using data from a population‐based register of CP. Children with suspected CP or who died before 1 year of age and those with CP of postneonatal origin were excluded. Prevalence of CP was 2.2 per 1000 live births without significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
10
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 22 publications
4
10
1
Order By: Relevance
“…In our study, which used a different measure of severity, the proportion of most severe cases of CP (LAS≥70%) in the second half of the study period was about 60% lower in VLBW infants than in those weighing ≥2500 g, but it was not statistically significant (p=0.06). The findings of our study were consistent with other studies for normal birth weight and term infants, showing a stable prevalence of CP during the 1990s 7 8. For moderately LBW infants (1500–2499 g), as in other studies,7 our CP rates declined in all severity groups but the trends were not statistically significant.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In our study, which used a different measure of severity, the proportion of most severe cases of CP (LAS≥70%) in the second half of the study period was about 60% lower in VLBW infants than in those weighing ≥2500 g, but it was not statistically significant (p=0.06). The findings of our study were consistent with other studies for normal birth weight and term infants, showing a stable prevalence of CP during the 1990s 7 8. For moderately LBW infants (1500–2499 g), as in other studies,7 our CP rates declined in all severity groups but the trends were not statistically significant.…”
Section: Discussionsupporting
confidence: 92%
“…As in our study, Northern Ireland found no significant change in rate of CP for 1981–1997 births; however our rates of CP for VLBW infants (<1500 g) were higher at about 75 per 1000 than Northern Ireland's at 44.5 per 1000 8. This may be partially explained by our use of neonatal survivors rather than live births as denominators.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…Further, of the 1649 infants identified as having CP, nearly one quarter ( n = 381) were identified as having an IQ less than 50 (Pharoah et al 1998). In a longitudinal study of 909 individuals with CP, 44 % had an IQ less than 70, and 26 % had an IQ less than 50 (Dolk et al 2006). The results of an international study of CP reported that 23-44 % of the CP population studied had an IQ less than 70 (Cans, 2000).…”
Section: Prevalencementioning
confidence: 96%
“…Specifically, the likelihood of CP has been demonstrated to increase as birth weight decreases. In comparison to the rates of CP overall (2-3 per 1000; Himmelmann et al 2005;SCPE 2000), Dolk et al (2006) observed a prevalence rate of 44.5 per 1000 live births when infants weighed less than 1500 g. Some researchers have also identified socioeconomic status (SES) as a significant factor in CP prevalence (Brooks-Gunn et al 1996;Yeargin-Allsopp et al 1995). A study in the United Kingdom identified significantly lower rates of CP (2.08 per 1000) in high SES families when compared to low SES families (3.33 per 1000; Dolk et al 2001;Dowding and Barry 1990).…”
Section: Contributing Factorsmentioning
confidence: 98%